2016
DOI: 10.1136/bmjopen-2016-013176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alcohol use on mortality and expenditure during hospital admission: a cross-sectional study

Abstract: ObjectivesThis study was designed to investigate the effect of alcohol intoxication on clinical presentation of hospitalised adult trauma patients at a Level I trauma centre using propensity score matching.DesignCross-sectional study.SettingTaiwan.ParticipantsDetailed data of 929 hospitalised adult trauma patients with alcohol intoxication, aged 20–65 years, and 10 104 corresponding patients without alcohol intoxication were retrieved from the Trauma Registry System between 1 January 2009 and 31 December 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In this study, patients were predominantly male of younger age .This agrees with a study by Peng S-H, et al [20] .The gender distribution showed an overall male to female ratio of 4:1 and those in the age group mostly affected were between 29 and 38 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, patients were predominantly male of younger age .This agrees with a study by Peng S-H, et al [20] .The gender distribution showed an overall male to female ratio of 4:1 and those in the age group mostly affected were between 29 and 38 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] and Peng et al . [ 12 ] showed that a high percentage of males were intoxicated, 66.4% and 88.4%, respectively, in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by Peng et al . [ 12 ] and Demetriades et al . [ 19 ] showed a high AIS score for intoxicated patients.…”
Section: Discussionmentioning
confidence: 99%